2013
DOI: 10.5713/ajas.2013.13094
|View full text |Cite
|
Sign up to set email alerts
|

Rumen Fermentation and Performance of Lactating Dairy Cows Affected by Physical Forms and Urea Treatment of Rice Straw

Abstract: The aim of this study was to determine the effect of different physical forms and urea treatment of rice straw on feed intake, rumen fermentation, and milk production. Four, multiparous Holstein crossbred dairy cows in mid-lactation with initial body weight (BW) of 409±20 kg were randomly assigned according to a 4×4 Latin square design to receive four dietary treatments. The dietary treatments were as follows: untreated, long form rice straw (LRS), urea-treated (5%), long form rice straw (5% ULRS), urea-treate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 47 publications
1
5
1
Order By: Relevance
“…The ruminal pH in control was significantly lower than those of treatment group. However, mean ruminal pH was not altered by dietary treatments and was in optimal range for the ecology and fermentation by microbes as reported by Gunun et al (2013) . Rumen NH 3 -N concentrations varied in response to feeding, especially at the peaks occurring at 3 h post-feeding.…”
Section: Discussionsupporting
confidence: 64%
“…The ruminal pH in control was significantly lower than those of treatment group. However, mean ruminal pH was not altered by dietary treatments and was in optimal range for the ecology and fermentation by microbes as reported by Gunun et al (2013) . Rumen NH 3 -N concentrations varied in response to feeding, especially at the peaks occurring at 3 h post-feeding.…”
Section: Discussionsupporting
confidence: 64%
“…It may also be as a result that the rams fed UTGNS and LGNS had a better nutrient absorption and utilization which resulted in a significantly higher weight gain and daily weight gain as compared to those fed UGNS or ULGNS (McDonald et al, 2010). Higher feed intake observed in this study with UTGNS was in conflict with the reports described by some authors (Gunun et al, 2013a(Gunun et al, , 2013bWanapat et al, 2013), who found out that the DM (dry matter) of treated rice straw improved the intake of dairy cows related to untreated rice straw. The authors also reported that urea-lime treatment could have the highest results among all treatments which was in conflict with the present study.…”
Section: Growth Performance For Yankasa Rams Fed Experimental Dietscontrasting
confidence: 99%
“…This is an indication that there was no kidney dysfunction or the diets provided adequate protein for the animals (Aruwayo, et al, 2011). The higher values of blood urea nitrogen for rams receiving UGNS diets in this study might be as a result of high release of ammonia in the rumen resulting to high absorption of ammonia from the rumen into the blood (Abubakar et al, 2010;Gunun et al, 2013b;Nayawo et al, 2017). Also, Yadav and Yadav (1988) reported increased in blood urea in cattle fed treated straw compared to the untreated.…”
Section: Serum Biochemical Parameters In Yankasa Rams Fed Experimentamentioning
confidence: 72%
“…Spraying urea on wheat straw improved DM digestibility and rumen N utilization (Bravo, Arelovich, Storm, Martínez, & Amela 2008). Although HFF are mainly used with low requirement animals, recently a mix of urea plus calcium hydroxide (Wanapat, Polyorach, Boonnop, Mapato, & Cherdthong, 2009) or a combination of urea plus a forage particle reduction (Gunun, Wanapat, & Anantasook, 2013) applied to rice straw improved intake, rumen dry-matter digestion and milk production in lactating dairy cows. In this study, we focused on various forage species as well as some crop residues with different chemical and delignification agents alone or in combination.…”
Section: Introductionmentioning
confidence: 99%